Analisis Kemampuan Konsentrasi Siswa Terhadap Pembelajaran Bahasa Indonesia Pada Siswa Kelas IV SD Negeri 11 Tanjung Batu - Puteri Anugrah; Ramanata Disurya; Farizal Imansyah (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The purpose of this research is to analyze students' concentration abilities in learning Indonesian in class IV students at SD Negeri 11 Tanjung Batu. The research method uses descriptive qualitative. By using observation, interviews and documentation instruments. The research subjects were fourth grade students at SD Negeri 11 Tanjung Batu. The results of the research show that the majority of class IV students have a fairly good level of concentration ability, however there are several factors that influence students' concentration abilities such as the learning environment, teaching methods, and students' internal factors. It was found that students tend to focus more on learning material that interests them, and interactive teaching methods can increase concentration levels. to improve students' concentration abilities includes more varied and interesting teaching methods, increasing the role of teachers in creating a conducive learning environment, and involving parents to support learning at home. It is hoped that this research can make a positive contribution to efforts to improve the quality of Indonesian language learning at the elementary school level, especially at SD Negeri 11 Tanjung Batu. Keywords : Analysic of concentration and Indonesia language skills.